A qualidade da permanência como estratégia de assistência estudantil: o caso do Programa Institucional de Bolsas da Universidade Federal de Lavras - Botelho, Rossano Wagner de Lima (2019)
It is a relatively recent fact to regulate student assistance in the governmental sphere, admitting it as a public policy. The phase of the expansion of student assistance is inaugurated as of the approval of the National Plan for Student Assistance/PNA in 2007, under the sign of the discourse of democratization, in the wake of the institutionalization of REUNI in 2006. The search path seeks to identify the particularities of university reforms, especially those of the 2000s, and to analyze the possible links between the expansion of student assistance and the REUNI proposals and the ENEM / SISU "system". By means of the critical analysis of secondary data referring to the years 2000, arranged in the reports of the MEC, in the legislations of REUNI and of the ENEM / SISU system; and the analysis of the regulation of student assistance when implementing PNAES, and considering the historical process of construction of this policy, it is intended to reflect the various facets that student assistance has assumed in its historical course, seeking to systematize the main points of discussion and the current issue. Thus, the research aims at apprehending the main determinants that make up the expansion of student assistance in the 2000s and, through the analysis of student assistance as a way to reduce dropout in higher education, its effect on success rate and academic performance the following question: what are the contributions of the Institutional Scholarship Program of the Federal University of Lavras for the quality of student stay in UFLA? From quantitative research, with experimental nature and referring to the period from 2013 to 2018, it was shown that the UFLA Institutional Scholarship Program has a positive effect in relation to reduction of dropout, academic performance and on the success rate of their beneficiaries.